2017
DOI: 10.20344/amp.7919
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Family Functioning and Neuroendocrine Biomarkers in Obese Children

Abstract: Material and Methods:A non-random sample of 104 obese children (55 boys), mean age 10.9 years (standard deviation 1.76), was recruited from a childhood obesity clinic. Obesity was defined as body mass index above the 95 th age-and gender-specific percentiles. Neuroendocrine biomarkers were measured. Symptoms of anxiety and depression were assessed with self and parent-reported questionnaires (Anxiety, Depression and Stress Scales; Child Behaviour Checklist). Family functioning was assessed with parent-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the dimension related to the subjective perception of eating habits, the variables retained in the final estimation model were the caretaker's perception of the child's food intake while worried, irritated, or anxious and the caretaker's perception of the adequacy for age of the child's usual food intake. Previous studies have shown psychopathology to be associated with overweight in children [54,55]; validity data indicate that children as young as 4 years old can report on their own anxiety symptoms [56]. In reaction to anxiety, emotional eating acts as a biological response that provides temporary feelings of gratification/satisfaction [57].…”
Section: Subjective Perception Of Eating Habits Dimensionmentioning
confidence: 99%
“…In the dimension related to the subjective perception of eating habits, the variables retained in the final estimation model were the caretaker's perception of the child's food intake while worried, irritated, or anxious and the caretaker's perception of the adequacy for age of the child's usual food intake. Previous studies have shown psychopathology to be associated with overweight in children [54,55]; validity data indicate that children as young as 4 years old can report on their own anxiety symptoms [56]. In reaction to anxiety, emotional eating acts as a biological response that provides temporary feelings of gratification/satisfaction [57].…”
Section: Subjective Perception Of Eating Habits Dimensionmentioning
confidence: 99%
“…The Nutritional Survey of the Spanish Population (ENPE in its Spanish abbreviation) carried out in people aged 3-24 years, found a frequency of excess weight and obesity of more than 50%; of these individuals, 71.6% presented abdominal obesity (Aranceta-Bartrina et al, 2016). In addition, excess weight in childhood is associated with obesity in adulthood and the development of metabolic and cardiovascular comorbidities including diabetes mellitus, arterial hypertension, dyslipidemia, metabolic syndrome, and non-alcoholic fatty liver (Oses et al, 2019;Ward et al, 2017), and psychological disorders such as depression or anxiety (Pinto et al, 2017;Quek et al, 2017).…”
mentioning
confidence: 99%